Developing Two Tier Test of Critical Thinking Ability using Rasch Model - Novika Lestari; Chairun Nisa; Mutazam Mutazam; Soeharto Soeharto (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
Critical thinking ability refers to cognitive processes to solve problems so that students are able to relate learning to everyday life. This achievement needs to be measured with valid and reliable instruments. Therefore, the research was conducted with the aim of characterizing the critical thinking test type two tier tests using the Rasch model. This study used a construction design and test validation. The construction process resulted in a critical thinking test of the two-tier type in the form of multiple choice on physics material for class X semester 1 which measured three basic aspects of critical thinking. The validation procedure was based on a trial exam taken by 146 students in Melawi Regency and a test evaluation by two experts. The findings demonstrated that the Aiken's V content validity analysis and the analysis utilizing item response theory both supported the validity of the critical thinking test. The analysis's findings demonstrated the validity and reliability of this test of critical thinking. The 23 created questions were found to be valid based on the results of the content validity test utilizing Aiken V. This test's empirical validity demonstrates that every item has a good level of difficulty and meets the Rasch model. The physics material used in the designed critical thinking test for class X semester 1 was valid, dependable, and had a good level of difficulty.